Factors influencing changes in body composition and nutritional status in patients with hyperacute stroke: prospective study - Hiroshi Irisawa; Tomoyuki Nakamura; Yumi Chiba; Mitsuki Hirota; Hajime Hoshiai; Takashi Mizushima (Frontiers in Nutrition)
Background and aimsMuscle loss not only reduce the effectiveness of the recovery period of rehabilitation after stroke but also prolongs the length of hospital stay. Therefore, it is crucial to maintain muscle mass during the hyperacute phase of stroke. We aimed to investigate the factor that influence changes in muscle mass and quality in patients with hyperacute stroke by using a body composition analyzer.MethodsBody composition assessment was performed on 156 patients admitted to the stroke care unit at the time of admission and 1 week later. Additionally, associations between rehabilitation intervention time, nutritional dosage and administration method, and stroke severity were examined to which factors were affecting body composition.ResultsMuscle mass and quality significantly decreased in both men (SMI: 7.41 ± 1.26 to 7.22 ± 1.23 kg/m2, p < 0.005, phA: 5.5 ± 1.24 to 5.31 ± 1.29 degree, p < 0.005) and women (SMI: 6.04 ± 1.30 to 5.08 ± 1.20 kg/m2, p < 0.005, phA: 4.58 ± 0.85 to4.18 ± 0.82 degree, p < 0.005)1 week after admission. Rehabilitation intervention time [odds ratio (OR) = 2.12; 95% CI: 1.28–4.47, p = 0.01], and high calorie dosage (OR = 1.53; 95% CI: 1.14–3.21, p = 0.03) significantly reduced the loss of muscle mass. However, stroke severity did not affect variations in body composition.ConclusionDeterioration in muscle mass and quality was observed during the hyperacute phase of stroke. The risk of muscle mass loss may be reduced with appropriate rehabilitation intervention and diet therapy from the early stage of hospitalization. Therefore, providing early rehabilitation intervention and nutritional management in the hospitalization phase are important to improve treatment effectiveness. In hyperacute stroke treatment, rehabilitation and nutritional administration should be provided as early as possible.Clinical trial registrationhttps://center6.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000053017, identifier UMIN-CTR UMIN000046467.